IoT-based motor speed monitoring using infrared sensor - Hakim, Abdullah; Effendi, Hansi; Yelfianhar, Ichwan; Elvanny Myori, Dwiprima (Journal of Industrial Automation and Electrical Engineering, 2024)
This paper presents the design and development of an Internet of Things (IoT)-based system for monitoring the speed of DC motors. Utilizing an ESP32 microcontroller integrated with infrared sensors, the system accurately measures motor speed by detecting pulses from a five-pointed star wheel attached to the motor shaft. The Arduino framework and Blynk platform are employed for real-time data visualization and remote monitoring. The system supports multiple motors, transmitting speed data to a cloud server via WiFi, allowing users to monitor performance remotely. Debouncing techniques and a moving average filter enhance data accuracy, while a correction factor refines RPM calculations. Threshold alerts notify users of excessive speeds, enabling proactive maintenance. This scalable solution is ideal for industrial applications requiring real-time monitoring and data-driven insights